Production and operations management : manufacturing and services - Dilworth, James B. (New York : McGraw Hill Education, 1993)
Shows students how managers plan and control operations for optimum productivity, quality and customer satisfaction in both manufacturing and service industries. This revision reflects significant current issues, changing technologies and the globalization of production.
Part 1: Foundation material; zeroing in on operations; operations strategy; forecasting demand. Part 2: Planning and controlling operations; planning for operations and capacity; overview of materials management; managing independent-demand inventory; managing dependent-demand items and capacity; scheduling and controlling manufacturing; just-in-time manufacturing or manufacturing excellence; the nature and scheduling of services; scheduling and controlling projects; total quality management; statistical quality control. Part 3: Design of operations systems; facility location; layout of facilities; design and manage for technological advantage; job design; work measurement and compensation; the future.
Includes index.
Keywords: PRODUCTION MANAGEMENT